Stimulating Competencies through Problematic Situations - Fadel , Mohamed Rafik (Journal of Human Sciences, 2021)
Teachers have often expressed their frustration when confronted to problematic situations which prevent them from achieving their plans and consequently fulfilling their objectives. This feeling is often due to the fact that these teachers have all developed knowledge and acquired skills in safe and comfortable settings during their training. They have rarely been, if ever, introduced to the development of skills in problematic situations. Their frustration can be avoided if they develop problem solving competencies as part of their training. We believe this is a major role of teacher trainers who should take in charge this issue seriously. This paper aims at suggesting a teaching methodology to stimulate problem solving competencies through problematic situations in teacher education.